Prevalence and factors associated with fear of childbirth in late pregnancy: a cross-sectional study - Dongning He; Dongning He; Jinling Zhang; Jinling Zhang; Guoyu Wang; Guoyu Wang; Yan Huang; Yan Huang; Na Li; Na Li; Mingxin Zhu; Mingxin Zhu; et al. (Frontiers in Public Health)
BackgroundFear of childbirth is a common concern among pregnant women, potentially affecting maternal physical and mental health as well as birth outcomes. However, the factors influencing fear of childbirth are still being explored. This study aims to assess the prevalence of fear of childbirth among women in late pregnancy and identify associated factors, with a particular focus on pregnancy comorbidities, complications, and specific obstetric conditions.MethodsA cross-sectional study was conducted from October 2022 to March 2024 at a tertiary women’s and children’s hospital in western China. A total of 6,335 pregnant women were recruited. The Childbirth Attitude Questionnaire was used to measure fear of childbirth. Data on pregnancy comorbidities, complications, and specific obstetric conditions were extracted from the hospital information system. Ordinal logistic regression was performed to analyze factors associated with different levels of fear of childbirth.ResultsThe mean score of the Childbirth Attitude Questionnaire was 34.69 ± 8.15. 79.8% of the participants reported mild to severe fear of childbirth in late pregnancy. Ordinal logistic regression analysis identified several significant risk factors for severe fear of childbirth, including lower education level, primiparity, no history of uterine scarring, natural conception, intention to have a cesarean section, high myopia, and urinary disease.ConclusionFear of childbirth is highly prevalent among women in late pregnancy and is influenced by multiple factors, including pregnancy comorbidities and complications. Obstetric healthcare providers should be aware of fear of childbirth and consider both sociodemographic and obstetric characteristics when implementing targeted interventions and counseling to support high-risk groups.